DEVELOPMENT OF MATHEMATICAL LITERACY SKILL INSTRUMENTS ON CIRCLE MATERIAL FOR JUNIOR HIGH SCHOOL STUDENTS - Hayati, Rohimatul; Yuhana, Yuyu (Journal of Authentic Research on Mathematics Education (JARME), 2024)
The importance of mathematical literacy skills is often not matched by the availability of supportive questions that aid in improving these abilities. Therefore, this study aims to develop valid and practical mathematical literacy questions specifically on the topic of circles, suitable for eighth-grade junior high school students. Employing the ADDIE model of research and development (RD), which includes analysis, design, development, implementation, and evaluation, the research involved 32 eighth-grade students as subjects. Instruments utilized included expert validation sheets, student response questionnaires, and a mathematical literacy test. Data analysis techniques encompassed both quantitative and qualitative analyses. Results from expert validation and student response questionnaires indicated that the developed instruments are both valid and practical. Expert validation tests achieved an 86% success rate overall, with 88% validity for material aspects, 88% for construction aspects, and 83% for language aspects. Validity testing, reliability testing, and item discrimination analysis confirmed the questions' validity, reliability, and appropriateness. The student response questionnaire yielded an 87% success rate, indicating high practicality for educational use. These findings demonstrate the effectiveness and applicability of the developed mathematical literacy questions in enhancing students' mathematical literacy skills and suggest their suitability for integration into the teaching process.